Politik identitas Muslim di Jerman dan Perancis - Jamil, Irpan; Setiadi, Ozi (State Islamic Institute of Kudus (IAIN Kudus), 2019)
The politics of Muslim identity in Germany and France. Islam is a universal religion. It became a religion that grew very rapidly in Europe. Germany and France are countries in Europe affected by Islamic growth. This happens because of many factors, such as the entry of Muslim immigrants, conversion to Islam, and others. This research, firstly, comprehensively describes the concept of Islamic political identity in Germany and France. Second, analyzing it in a descriptive-substantive way to find the ideal pattern of the concept of Islamic political identity in Germany and France. This type of research is a literature study with a qualitative approach to the nature of descriptive-analytical research. This study found that the development of Islam in Germany and France was supported by policies in favor of Muslims, specifically regarding the establishment of places of worship and social and cultural relations. However, the absence of formal religious infrastructure and dealing with secularization are something that needs attention. German and French Muslims make religious ideologies and symbols, such as mosques, their political endeavors.